2007
DOI: 10.1063/1.2749251
|View full text |Cite
|
Sign up to set email alerts
|

Car-Parrinello and path integral molecular dynamics study of the hydrogen bond in the chloroacetic acid dimer system

Abstract: We have studied the double proton transfer (DPT) reaction in the cyclic dimer of chloroacetic acid using both classical and path integral Car-Parrinello molecular dynamics. We also attempt to quantify the errors in the potential energy surface that arise from the use of a pure density functional. In the classical dynamics a clear reaction mechanism can be identified, where asynchronized DPT arises due to coupling between the O–H stretching oscillator and several low energy intermolecular vibrational modes. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…For each atom, the geometrical average of its position over all the beads is termed its centroid. Energy barriers and rates for reactions and transitions, including proton transfers, have previously been studied using PIMD techniques, [26][27][28][29] often via centroid molecular dynamics, [30][31][32][33][34][35] an approximate scheme that works with the centroids as classical dynamical variables, subject to a mean potential energy surface. Another PIMD-based scheme that has recently been used to estimate reaction rates and realtime correlation functions is the ring-polymer molecular dynamics method.…”
Section: Methodsmentioning
confidence: 99%
“…For each atom, the geometrical average of its position over all the beads is termed its centroid. Energy barriers and rates for reactions and transitions, including proton transfers, have previously been studied using PIMD techniques, [26][27][28][29] often via centroid molecular dynamics, [30][31][32][33][34][35] an approximate scheme that works with the centroids as classical dynamical variables, subject to a mean potential energy surface. Another PIMD-based scheme that has recently been used to estimate reaction rates and realtime correlation functions is the ring-polymer molecular dynamics method.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that the accuracy of the PES in Car-Parrinello simulations is determined by the exchange and correlation functionals used. For the CPMD studies of acetic acid dimer in the gas phase we have show that underestimation of barrier height for proton transfer due to use of DFT formalism is approximately compensated by neglecting the zero point vibrational contribution in simulations [29].…”
Section: Resultsmentioning
confidence: 94%
“…It is important to note that the accuracy of the PES in CarParrinello simulations is determined by the exchange and correlation functionals used. For the CPMD studies of chloroacetic acid dimer in the gas phase we have shown that underestimation of barrier height for proton motion due to the use of DFT formalism is approximately compensated by neglecting of the zero-point vibrational contribution in simulations [33].…”
Section: Resultsmentioning
confidence: 98%